Peningkatan Performansi Cooling Tower Tipe Induced Draft Counter Flow Menggunakan Variasi Bentuk Filler - Eky Novianarenti; Gatot Setyono (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to build and test a cooling tower. Cooling tower is a heat exchanger that functions to cool the hot water from the condenser and throw heat into the atmosphere at a power plant. This is done so that the temperature of the hot water from the condenser can cool as the original condition. One component of the cooling tower compiler is filler. Filler is a component that is very influential on cooling tower performance, where the contact surface between water and air is expanded and the contact time is extended. The study was conducted experimentally using the NTU (Number of Transfer Unit) method. The variations made in this study are straight filler, zig zag, and wavy shape. The parameters observed are the rate of heat transfer, cooling tower capacity and the effectiveness of the cooling tower.